Bóg-człowiek, bóg-zwierzę. Zwierzęce twarze religii - Mitek-Dziemba, Alina (Zoophilologica. Polish Journal of Animal Studies, 2015)
The aim of this short article is to discuss the state of research in a field which attempts to combine animal studies with theology and religious studies, and to map its discourse, tentatively called “critical ecotheology” and construed as environmental ethics accompanied by a religious inspiration and theological justification which is derived from dogmas and religious attitudes of different world religions. The attempt at providing a theoretical framework for ecotheology was inspired by the pioneering work of scholars who came in September 2014 to Bonn, Germany, for a conference on human-animal relations in religious traditions. The problems brought up by their presentations provoked a discussion of the presence of animals in the thinking, practices, and rituals of various religions and their theologies, highlighting the role of religious culture in negotiating different senses of the animal. The article concludes with the idea that a review of religious and theological issues from the perspective of animal studies may lead to the revision of many concepts and theoretical paradigms within the history and anthropology of religion, while helping to articulate the significance of animals and the need for their protection in the activity of religious groups and individuals.